2018
DOI: 10.1007/s11109-018-9455-7
|View full text |Cite
|
Sign up to set email alerts
|

The Curse of Knowledge? Education, Corruption, and Politics

Abstract: Education has consistently been found to be positively related to political participation, electoral turnout, civic engagement, political knowledge, and democratic attitudes and opinions. Previous research has, however, not sufficiently acknowledged the large existing between-and within-country variations in institutional quality when studying this relationship. This study asks the question: how do highly educated, well-informed, and critical citizens react to a political system with low-quality institutions; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
(115 reference statements)
1
23
0
1
Order By: Relevance
“…We here examine a potential piece in this puzzle by examining how the links between corruption perceptions and political participation differ for men and women. Previous studies show that the effect of perceptions of corruption differ across social groups (Agerberg 2019;Bazurli and Portos 2019), but the differences between men and women remain unclear. It has been a cause for concern that previous research has found a consistent gender gap in political participation (Dalton 2017;Verba, Schlozman, and Brady 1995).…”
Section: 行分析。我们的结果显示,当面对腐败时,女性变得更有可能参与 投票,而男性则在面对腐败时更有可能进行以挑战精英为形式的参 mentioning
confidence: 99%
“…We here examine a potential piece in this puzzle by examining how the links between corruption perceptions and political participation differ for men and women. Previous studies show that the effect of perceptions of corruption differ across social groups (Agerberg 2019;Bazurli and Portos 2019), but the differences between men and women remain unclear. It has been a cause for concern that previous research has found a consistent gender gap in political participation (Dalton 2017;Verba, Schlozman, and Brady 1995).…”
Section: 行分析。我们的结果显示,当面对腐败时,女性变得更有可能参与 投票,而男性则在面对腐败时更有可能进行以挑战精英为形式的参 mentioning
confidence: 99%
“…Transparency International estimates that over 80 % of the world's population live in countries where corruption is a very serious problem. 2 Research shows that startlingly poor public institutions can be 1 INTRODUCTION found, for instance, at the heart of western Europe, in what many consider among the most 'developed' parts of the world (Charron et al 2013). A growing literature in political science has, in the light of this, started to ask questions about how differences in institutional quality shape and structure citizens' political attitudes and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Providing further evidence for an interaction between democratic quality and education, Ugur-Cinar et al (2020) show that education and political trust are positively correlated in countries with low levels of corruption but that in highly corrupt countries, the more highly educated express less trust in political institutions than the less educated. Similarly, Agerberg (2019) finds education to have a weaker positive effect on what he calls "institutional attitudes" in democracies with high levels of corruption, indicating that corruption has a stronger negative effect on citizens' attitudes among the higher educated. Overall, we can therefore expect the indirect effect of democratic quality on political trust to be larger for more highly educated citizens.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%